Pengaruh Reward dan Punishment Terhadap Motivasi Kerja Karyawan Dalam Menyelesaikan Target Perusahaan (Studi Pada PT. Amaan Indonesia Sejahtera Kota Tulungagung) - Sustiyatik, Enni; Sari, Wisma Fiana (JURNAL APLIKASI PELAYARAN DAN KEPELABUHANAN, 2023)
This study aims to determine how much influence reward has on employee motivation, how much influence punishment has on employee motivation in completing targets given by the company where the employee works. This study uses descriptive quantitative and inferential types with data collection techniques, namely distributing questionnaires to 90 respondents, which is the population of the research object, namely all employees of PT Amaan Indonesia Sejahtera, Tulungagung City Branch Office and using the census method. The results of this study indicate that: (1) reward has a positive and significant effect on employee motivation (2) punishment has a positive and significant effect on employee motivation (3) the results of the F test state that the variables of reward and punishment simultaneously affect employee motivation. And the value of the coefficient of determination (R2) is 57.2%. This research recommends that PT. Amaan Indonesia Sejahtera Tulungagung city branch office maintains the quality of employee performance so that it can produce competitive employees.